Effect of Trunk Training on Dynamic Balance in Chronic Stroke Survivor - Maria Samad, Binash Afzal, Amna Ali, Faiza Altaf, Ambreen Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Stroke leads to muscle paresis, balance and postural control deficits. Balance instability is challenging problem in stroke survivor. Trunk control is prerequisite for balance either static or dynamic. Trunk training encompassed exercises to strengthen trunk muscles on a therapeutic mat (stable surface) and Swiss Ball (unstable surface). The objective was to estimate the effect of trunk training on dynamic balance in chronic stroke patient. The case was of 50 year old female patient with left hemiparesis. She had impaired trunk control and balance and assessed with Trunk Impairment Scale and Berg Balance Scale. The intervention comprised of trunk training of 40-50 minutes 3/week for four week. Trunk impairment scale and Berg balance scale score was improved post intervention which proposed that trunk training is useful to restore dynamic balance. Keywords: Stroke, Trunk Training, Balance